Political economy of state capacity - Ahrenshop, M-P (2023)
How does society react politically when the state tries to increase its capacity? This thesis presents three experimental studies that shed light on this question by examining the micro-behavioral consequences of such increases in state capacity. The first article explores how delegating tax collection to local elites such as city chiefs in the Democratic Republic of the Congo affects citizen demand for accountability, both from the state and the chiefs. It examines data collected from a randomized controlled trial in the city of Kananga where neighborhoods were assigned to either state or chief tax collection, and citizens had a collective action opportunity to hold both accountable through the request of citizen meetings. The results show that delegating tax collection to local elites does not impede citizens’ ability or willingness to hold both chiefs and the state accountable for policy outcomes. The second article asks whether there are electoral costs associated when candidates for political office promise to fight corruption instead of improving economic growth. The study draws on evidence from two conjoint experiments conducted in India and the United Kingdom where respondents could choose between different hypothetical candidates who varied along multiple dimensions. The results suggest that promising to fight corruption as a central policy platform may be electorally punished by voters compared to promising to improve the economy. The third article investigates the bottom-up accountability pressures in response to earmarking tax revenue for particular public expenditures. It does so by leveraging variation in the extent of citizens’ beliefs about the prevalence of earmarking in an online survey experiment conducted in Ghana. Results show that earmarking revenue does not have positive accountability effects by virtue of increasing citizens’ incentives to engage in politics. Overall, this thesis contributes original data, novel evidence and new theoretical frameworks to the study of state-society relations and the political economy of state capacity.